An analog of Friedel oscillations in nanoconfined water. Issue 9 (29th November 2021) - Xue, Minmin; Hu, Zhili; Qiu, Hu; Shen, Chun; Guo, Wanlin; Zhang, Zhuhua
Abstract: Water confined in nanometer-scale crevices and cavities underpins a wide range of fundamental processes, such as capillary flow, ion transport and protein folding. However, how water responds within these confined spaces, with prevalent inhomogeneity built in or caused by impurities, is not well understood. Here, we show theoretically that water confined in one-dimensional nanochannels with localized perturbation exhibits pronounced density oscillations. The oscillations occur vividly like the Friedel oscillations in electron density resulting from defects in metals. A model analysis reveals that the density oscillations result from the perturbation-induced molecular scattering that is augmented by the confinement-enhanced correlation of water dipoles. This renders the oscillations a general behavior independent of the channel geometries and specific forms of the perturbation. Under confinements comparable to biological ion channels, such oscillations can strikingly extend over 10 nm, resulting in non-trivial effects at large distances that, for example, repel all ions from the channels with their long-range force. These results deepen the understanding of biological functions and inspire new applications in a variety of domains, such as ionic sensing and seawater desalination. Abstract : Water confined in nanochannels with localized perturbations exhibits Friedel-like density oscillations that can repel ions from the channels with their long-range force, with implication for applications in ionic sensing and seawater desalination.